Direct and maternal (co)variance components and genetic parameters for growth and reproductive traits in the Boran cattle in Kenya - Wasike, C.B.; Indetie, D.; Ojango, Julie M.K.; Kahi, A.K. (Springer, 2009)
Direct and maternal (co)variance components and genetic parameters were estimated for growth and reproductive traits in the Kenya Boran cattle fitting univariate animal models. Data consisted of records on 4502 animals from 81 sires and 1010 dams collected between 1989 and 2004. The average number of progeny per sire was 56. Direct heritability estimates for growth traits were 0.34, 0.12, 0.19, 0.08 and 0.14 for birth weight (BW), weaning weight (WW), 12-month weight (12W), 18-month weight (18W) and 24-month weight (24W), respectively. Maternal heritability increased from 0.14 at weaning to 0.34 at 12 months of age but reduced to 0.11 at 24 months of age. The maternal permanent environmental effect contributed 16%, 4% and 10% of the total phenotypic variance for WW, 12W and 18W, respectively. Direct-maternal genetic correlations were negative ranging from −0.14 to −0.58. The heritability estimates for reproductive traits were 0.04, 0.00, 0.15, 0.00 and 0.00 for age at first calving (AFC), calving interval in the first, second, and third parity, and pooled calving interval. Selection for growth traits should be practiced with caution since this may lead to a reduction in reproduction efficiency, and direct selection for reproductive traits may be hampered by their low heritability.